High Coral Bycatch in Bottom-Set Gillnet Coastal Fisheries Reveals Rich Coral Habitats in Southern Portugal - Dias, Vítor; Oliveira, Frederico; Boavida, Joana; Serrão, Ester A.; Gonçalves, Jorge M. S.; Coelho, Márcio A. G. (Frontiers in Marine Science, 2020)
Bottom-contact fisheries are unquestionably one of the main threats to the ecological integrity and functioning of deep-sea and circalittoral ecosystems, notably cold-water corals (CWC) and coral gardens. Lessons from the destructive impact of bottom trawling highlight the urgent need to understand how fisheries affect these vulnerable marine ecosystems. At the same time, the impact of other fishing gear and Small-Scale Fisheries (SSF) remains sparsely known despite anecdotal evidence suggesting their impact may be significant. This study aims to provide baseline information on coral bycatch by bottom-set gillnets used by artisanal fisheries in Sagres (Algarve, southwestern Portugal), thereby contributing to understand the impact of the activity but also the diversity and abundance of corals in this region. Coral bycatch frequency and species composition were quantified over two fishing seasons (summer-autumn and spring) for 42 days. The relationship with fishing effort was characterized according to métiers (n=6). The results showed that 85% of the gillnet deployments caught corals. The maximum number of coral specimens per net was observed in a deployment targeting Lophius budegassa (n=144). In total, 4,326 coral fragments and colonies of 23 different species were captured (fishing depth range of 57-510m, mean 139±8m). The most affected species were Eunicella verrucosa (32%), Paramuricea grayi (29%), Dendrophyllia cornigera (12%) and Dendrophyllia ramea (6%). The variables found to significantly influence the amount of corals caught were the target species, net length, depth and mesh size. The 22 species of corals caught as bycatch belong to Orders Alcyonacea (80%), Scleractinia (18%), Zoantharia (1%) and Antipatharia (1%), corresponding to around 13% of the coral species known for the Portuguese mainland coast. These results show that the impact of artisanal fisheries on circalittoral coral gardens and CWC is potentially greater than previously appreciated, which underscores the need for new conservation measures and alternative fishing practices. Measures such as closure of fishing areas, frequent monitoring onboard of fishing vessels or the development of encounter protocols in national waters is a good course of action. This study highlights the rich coral gardens of Sagres and how artisanal fisheries can pose significant threat to corals habitats in certain areas.